Concomitant Chronic Lymphocytic Leukemia and Mantle Cell Lymphoma Discovered by Flow Cytometry. (28th October 2020) - Erickson, K M; Lynch, D
Abstract: Casestudy : Chronic lymphocytic leukemia (CLL) accounts for about 30% of all lymphoid neoplasms and is the most common adult blood cancer in the Western world. Mantle cell lymphoma (MCL) accounts for only about 6% of all B-cell lymphomas in Western countries. MCL and CLL are both CD5 positive B-cell lymphoproliferative disorders. It is necessary to distinguish these two entities as MCL is a more aggressive disease, and requires specific treatment. MCL and CLL can occur in one patient at the same time and is often termed a composite lymphoma. We present an 84-year-old female with a history of endometrial cancer who was found to have splenomegaly and lymphadenopathy. Flow cytometry was performed upon her peripheral blood specimen which demonstrated two distinct populations of abnormal light chain restricted B-cell populations. One population demonstrated kappa light chain restriction and was positive for CD45, CD19, CD20, CD5, CD38, FMC-7, and CD22, representing MCL. The other population showed dim lambda light chain restriction that was also positive for CD45, CD19, dim CD20, CD5, and CD23, representing CLL. FISH studies demonstrated t(11;14), and four common deletions or chromosome aneuploidy associated with CLL. These findings confirmed the dual populations of CLL and MCL. This is an interesting case because it is a very rare combination with only a few cases having been reported with two distinct cell populations in one patient at the same time.